The intake of selected foods by six‐year‐old Swedish children differs according to parental education and migration status. (20th January 2016) - Säfsten, Eleonor; Nyberg, Gisela; Elinder, Liselotte Schäfer; Norman, Åsa; Patterson, Emma
Abstract: Aim: Little is known about how parental migration status may be associated with children's diets. We examined whether the intake of selected foods by six‐year‐old children differed according to their parents' migration status, taking education level into account. Methods: This study used pooled baseline data from two clustered randomised controlled trials of A Healthy School Start, conducted in municipalities of low‐to‐medium socio‐economic status in Stockholm County, Sweden. The children's intake of selected healthy and unhealthy foods was reported by parents using the Eating and Physical Activity Questionnaire, and the children's height and weight were measured. Parental education and country of birth were self‐reported. Results: Data were available for 520 children. Low parental education was associated with significantly higher intakes of fruit, higher intakes of several unhealthy foods and lower intakes of vegetables. Children of parents born outside the Nordic region had higher intakes of all unhealthy foods as well as fruit and vegetables, even when adjusted for education. A negative association between high education and overweight was only seen in children of Nordic‐born parents. Conclusion: Parental migration status was a strong predictor of the intake of selected foods and was a stronger predictor than parental education. Abstract :